Coronary heart disease and risk factors in elderly population - A. E. Imaeva; E. M. Tuaeva; S. A. Shalnova; N. V. Kiseleva (Кардиоваскулярная терапия и профилактика)
The treatment and prevention events against cardiovascular diseases have changed the age population structure. As by forecast, in RF the part of population older than economically active age will increase to 29,1% by the year 2030, hence increasing prevalence of ischemic heart disease (CHD). Therefore, one of the main currents is assessment of risk factors impact on morbidity and mortality from CHD among elderly. One of specifics of elderly population is simultaneous presence of several factors that enhance each other. Nevertheless, the prevalence of arterial hypertension and obesity increase with the age, and part of smokers and those with hypercholesterolemia increases, and relation of mortality with some risk factors does weaken with the age. That is a “survival effect” — earlier mortality of persons with adverse prognosis. Therefore, the specifics of CHD course in elderly dictates for necessity of an approach development to complex and methodic healthcare management.